Polygonal surface processing and mesh generation tools for the numerical simulation of the cardiac function. (28th January 2021) - Fedele, Marco; Quarteroni, Alfio
Abstract: In order to simulate the cardiac function for a patient‐specific geometry, the generation of the computational mesh is crucially important. In practice, the input is typically a set of unprocessed polygonal surfaces coming either from a template geometry or from medical images. These surfaces need ad‐hoc processing to be suitable for a volumetric mesh generation. In this work we propose a set of new algorithms and tools aiming to facilitate the mesh generation process. In particular, we focus on different aspects of a cardiac mesh generation pipeline: (1) specific polygonal surface processing for cardiac geometries, like connection of different heart chambers or segmentation outputs; (2) generation of accurate boundary tags; (3) definition of mesh‐size functions dependent on relevant geometric quantities; (4) processing and connecting together several volumetric meshes. The new algorithms—implemented in the open‐source software vmtk —can be combined with each other allowing the creation of personalized pipelines, that can be optimized for each cardiac geometry or for each aspect of the cardiac function to be modeled. Thanks to these features, the proposed tools can significantly speed‐up the mesh generation process for a large range of cardiac applications, from single‐chamber single‐physics simulations to multi‐chambers multi‐physics simulations. We detail all the proposed algorithms motivating them in the cardiac context and we highlight their flexibility by showing different examples of cardiac mesh generation pipelines. Abstract : We propose a set of algorithms and tools aiming to facilitate and speed‐up the mesh generation process for cardiac geometries. The main novelties regard the polygonal surface processing, the boundary tags definition, the mesh‐size definition, and the volumetric mesh processing. The new algorithms can be combined with each other to create personalized application‐specific pipelines. We demonstrate the robustness and the flexibility of the proposed tools through various examples on different kinds of cardiac geometries.